Answers

2014-12-08T10:47:38+05:30
Secα + tanα = p  ......(1) [ given]
We know that, sec
²α-tan²α = 1
⇒ (secα + tanα)(secα-tanα) = 1
⇒  (secα-tanα) = 1/p ........... (2)
Adding (1) and (2)
2 secα = p + 1/p
Subtracting (2) from (1)
⇒2tanα = p - 1/p   

Now,  \frac{2tan\alpha}{2sec\alpha} =  \frac{p-  \frac{1}{p}  }{p +  \frac{1}{p} }

Sin\alpha =   \frac{p^2-1}{p^2+1}


0
2014-12-10T21:02:43+05:30
secα + tanα = p                  
We know  sec
²α-tan²α = 1
             ⇒  (secα + tanα)(secα-tanα) = 1
             ⇒  (secα-tanα) = 1/p
Adding 
    we get      p + 1/p = 2secα
Subtracting we get    p - 1/p = 2tanα
                             ⇒ 2 sinα.secα=p-1/p
                             ⇒ sinα(p+1/p)=p-1/p
                             ⇒ sin α=(p²-1)/(p²+1)
0